PEMODELAN MATEMATIKA SEIqInqR PADA PENYEBARAN COVID-19 - Masita; Darmawati; Fardinah (Journal of Mathematics: Theory and Applications, 2021)
Coronavirus is a disease that is transmitted to humans that usually causes respiratory tract infections, the common cold to serious illnesses. Currently, COVID-19 cases in Indonesia are increasing due to significant transmission in various regions and the entry of corona variants in Indonesia which spreads faster, therefore the number of deaths due to COVID-19 is also increasing and Indonesia has the highest death toll in the world. The purpose of this study is to build a model and analyze the SEIqInqR mathematical model there are two equilibrium points, namely disease-free and endemic. Model analysis was performed using the Routh-Hurwitz criteria to identify the eigenvalues. From the results of the analysis obtained that the disease-free equilibrium point will be stable if the value of R0 < 1 of the 0,004487 and the endemic equilibrium point will be stable if the value of R0>1 of this 4,303393 at the end of the study, a simulation model was given using the maple application.based on simulation results the disease will disapper and the disease will become epidemic